A Review About the Effects of Digital Competences on Professional Recognition; The Mediating Role of Social Media and Structural Social Capital - Javier De la Hoz-Ruiz; Rawad Chaker; Lucía Fernández-Terol; Marta Olmo-Extremera (Societies)
This article investigates how digital competences contribute to the production of social capital and professional recognition through a systematic review of international literature. Drawing on 62 peer-reviewed articles indexed in Web of Science, Scopus, and ERIC, the review identifies the most frequently mobilized theoretical frameworks, the predominant types and sources of recognition, and the associated dimensions of social capital. The findings reveal a growing emphasis on communicative and network-based digital competences—particularly digital communication, information management, and virtual collaboration—as key assets in professional contexts. Recognition is shown to take predominantly non-material, extrinsic, and visibility-oriented forms, with social media platforms emerging as central sites for the performance and circulation of digital competences. The results indicate that social media proficiency has become a central determinant of social recognition, favoring individuals who possess not only digital fluency but also the ability to strategically develop and mobilize their networks. This dynamic reframes signal theory in light of today’s platformed ecosystems: recognition no longer depends increasingly on one’s capacity to render competences legible, visible, and endorsed within algorithmically mediated environments. Those who master the codes of visibility and reputation-building online are best positioned to convert recognition into social capital and professional opportunity.